1972
DOI: 10.2172/4591356
|View full text |Cite
|
Sign up to set email alerts
|

Final report of the light armor materials program.

Abstract: This report covers the work performed on the August 1970 extension of the Advanced Research Projects Agency (ARPA) order 980. This effort was directed to ward the development of light armor materials. The 'nltial concepts behind the development of these materials 1-5 are described in previous LLL reports. Contents Foreword jfi Abstract Introduction 2 The Effect of Composition and Microstructure on Ballistic Performance of Be 2 B and Be 4 B 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…1. The work reported in a series of documents by Wilkins et al 12–16 and Landringham and Casey 17 is probably the earliest systematic description of the dynamic failure in the ceramic plate when impacted by a KE projectile. Using computer simulations, which became powerful tools in the study of ceramic failure under impact loading in the years up to now, 18–20 it has been shown that the failure initiated from the back side of the ceramic tile.…”
Section: Failure Of Ceramics Under Impactmentioning
confidence: 99%
“…1. The work reported in a series of documents by Wilkins et al 12–16 and Landringham and Casey 17 is probably the earliest systematic description of the dynamic failure in the ceramic plate when impacted by a KE projectile. Using computer simulations, which became powerful tools in the study of ceramic failure under impact loading in the years up to now, 18–20 it has been shown that the failure initiated from the back side of the ceramic tile.…”
Section: Failure Of Ceramics Under Impactmentioning
confidence: 99%
“…Different ceramic materials are commonly used for ballistic protection; they include some oxide ceramics (mostly, alumina ceramics with different contents of Al 2 O 3 ) and non-oxide ceramics (mostly carbides, nitrides, borides and their combinations) [1][2][3][4][5][6][7][8][9][10][11]. Despite elevated density (up to 3.95 g cm À3 ), alumina ceramics are widely used for ballistic protection as they provide relatively high physical properties and performance, low cost and an ability to be manufactured using a variety of methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-infiltrated composites, e.g. such as B 4 C/Al [2], Lanxide TM SiC/Al (which were produced some time ago) and some others, with a high integrity to ballistic impact are not widely used for ballistic protection due to high cost of their processing and equipment, and they may be prone to problems in manufacturing. Also these materials can be employed only against low-hardness mild steel projectiles (they cannot withstand hard steel and, moreover, WC threats), especially if these composites contain a rather high amount of bonding soft metallic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration is the increased hardness of tungsten (3.5 -5 GPa) compared to hardened steel (1.2 -3.9 GPa), which will influence the contribution that ductile deformation processes at the projectile tip make to the overall defeat procedure, perhaps shifting the ballistic performance of the ceramics tested to be more dependent on the erosion effects during [42] to promote the growth of large and abnormal grains in alumina but to have a limited coarsening effect in ZTA due to zirconia grain boundary pinning effects [43]. If not carefully controlled, this could lead to significant differences in the grain structure of each ceramic, which, along with differences in the amount of porosity and impurities, has been shown to have a significant influence on ballistic performance [4,37,44]. In addition to changing core mechanical / physical properties, pores, weak glassy-phases and grain boundary sites are defects from which fracture may readily propagate during ballistic contacts.…”
Section: A Comparison Of Prior Ballistic Experiments On Ztamentioning
confidence: 99%